1991
DOI: 10.1002/ceat.270140209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some operating variables on the flotation of aluminium particles

Abstract: The effects of impeller speed, air flow rate, cell concentration, agitator size and cell volume on the recovery of aluminium particles have been studied in a KHD Humboldt Wedge AG machine, using alkyl benzene sodium sulphonate paste as collector and pine oil as frother. The recovery yield increased with increasing impeller speed, air flow rate, cell concentration and cell volume, up to a certain range, whereafter it decreased. A decrease in the recovery yield was observed on increasing the agitator size. A mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The experimental results indicate that at higher airflow rates (8 L/min), the recovery of fine particles was stable. Abdo et al suggested that low airflow rates lead to lower recoveries due to the fact that the flow rate of water to the froth is decreased [95]. Moreover, low aeration rates can cause froth overloading, resulting in the drainage of particles located inthe froth back to the pulp.…”
Section: Effect Of Airflow Rate On Magnesite Flotationmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results indicate that at higher airflow rates (8 L/min), the recovery of fine particles was stable. Abdo et al suggested that low airflow rates lead to lower recoveries due to the fact that the flow rate of water to the froth is decreased [95]. Moreover, low aeration rates can cause froth overloading, resulting in the drainage of particles located inthe froth back to the pulp.…”
Section: Effect Of Airflow Rate On Magnesite Flotationmentioning
confidence: 99%
“…Moreover, low aeration rates can cause froth overloading, resulting in the drainage of particles located inthe froth back to the pulp. It should be also noted that high aeration rates can cause high turbulent conditions and deposition of particles in the flotation cell, thus lowering their recovery [95]. Moreover, the addition of an electrolyte in a solution leads to an increase in bubbles' surface potential, which means repulsive forces between bubbles and particles are promoted [89].…”
Section: Effect Of Airflow Rate On Magnesite Flotationmentioning
confidence: 99%
See 1 more Smart Citation